Población y sociedad en la España imperial - Margulis, Mario (El Colegio de México A.C., 1992)
This article focuses on the structural conditions that characterized imperial Spain in the sixteenth and seventeenth centuries, and their effect on the demography of the period. The author argues that the political, economic, and social contradictions prevalent in the nation -such as imperial expansion, the strengthening of the seigniorial system and that of the Church, the heavy tax burdens, and the decline of agriculture, among others- caused a lag in capital accumulation. This sum of contradictions helps explain the easy spread of epidemics and the high rate of mortality in Spanish territory.